P3.63 The prevalence and incidence of active syphilis in women in morocco, 1995–2016: model-based estimation and implications for sti surveillance. (8th July 2017) - Korenromp, Eline; Taylor, Melanie; Bennani, Aziza; El-Kettani, Amina; El-Rhilani, Houssine; Alami, Kamal; Rowley, Jane; Abu-Raddad, Laithe; Mahiane, Guy
Abstract : Introduction: In 2016, the World Health Assembly adopted the global strategy 2016–2021 for STI control through the health sector, with as impact target to reduce syphilis incidence by 90% from 2018 to 2030. We applied the Spectrum STI estimation tool to estimate national adult prevalence and incidence of active syphilis in Morocco currently and over 1995–2015, to inform its national HIV/STI strategy, target setting and program evaluation. Methods: Syphilis prevalence levels and trends were fitted through logistic regression to data from surveys in antenatal clinics conducted during 1996–2012, and among women attending family planning clinics. Prevalence data were adjusted for diagnostic test performance. Incidence was inferred from prevalence by adjusting for the average duration of infection with active syphilis. Rates estimated for ANC women were assumed to apply to the overall female adult (15–49 years) population. Results: In 2016, syphilis prevalence was estimated to be 0.56% (95% confidence interval, CI: 0.3%–1.0%). Around 21, 675 (10, 612–37, 198) new syphilis infections were estimated to have occurred in adult women in 2016. This is a decline from the prevalence estimate for 2000 of 1.38% (0.87%–2.1%). Conclusion: Periodic population-based surveys allowed Morocco to estimate syphilis prevalence and incidence trends. The latest survey was done in 2012 and so the trends are relatively uncertain after 2012, when no new surveys were conducted. Planned recording of results from routine antenatal programmatic screening, being rolled out from 2017, should soon allow updating and re-calibration of future estimations.